2019
DOI: 10.1111/head.13475
|View full text |Cite
|
Sign up to set email alerts
|

Topical Ambroxol 20% for the Treatment of Classical Trigeminal Neuralgia – A New Option? Initial Clinical Case Observations

Abstract: Background Trigeminal neuralgia is difficult to treat and shows upregulation of sodium channels. The expectorant ambroxol acts as a strong local anesthetic, about 40 times stronger than lidocaine. It preferentially inhibits the channel subtype Nav1.8, expressed especially in nociceptive C‐fibers. It seemed reasonable to try ambroxol for the treatment with neuropathic facial pain unresponsive to other standard options. Material and Methods Medical records of patients suffering from classical trigeminal neuralgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 85 publications
0
11
0
2
Order By: Relevance
“…Since no preventive therapies have shown significant clinical efficacy for CIPN, drug repurposing may offer an alternative therapeutic option [7]. Previously, it was shown that ambroxol, a mucolytic agent used for the treatment of various respiratory system diseases, is effective as a repurposed drug in numerous neuropathic pain states in humans [34,[74][75][76][77]. Additionally, our previous research confirmed that it might attenuate cold hypersensitivity in mice treated with oxaliplatin [78].…”
Section: Discussionmentioning
confidence: 88%
“…Since no preventive therapies have shown significant clinical efficacy for CIPN, drug repurposing may offer an alternative therapeutic option [7]. Previously, it was shown that ambroxol, a mucolytic agent used for the treatment of various respiratory system diseases, is effective as a repurposed drug in numerous neuropathic pain states in humans [34,[74][75][76][77]. Additionally, our previous research confirmed that it might attenuate cold hypersensitivity in mice treated with oxaliplatin [78].…”
Section: Discussionmentioning
confidence: 88%
“…Schnell et al describe the use of IV phenytoin for trigeminal neuralgia crises, adding to the literature on this often difficult‐to‐treat presentation 11 . Lastly, Kern et al report a small series of trigeminal neuralgia patients who responded to topical ambroxol 20%, an expectorant with local anesthetic properties considered approximately 40 times stronger than lidocaine 12 . Importantly, the ambroxol series was open‐label, and the authors did not specify the total number of trigeminal neuralgia patients treated, making it difficult to assess their overall responder rate 13 .…”
Section: Additional Nosological Complexitiesmentioning
confidence: 99%
“…Studies selected for this virtual issue address the clinical presentation, diagnostic considerations, classification, and treatment of trigeminal neuralgia and explore complexities associated with the diagnosis of facial pain within the current classification system. This virtual issue begins with an excellent and detailed over- 12 Importantly, the ambroxol series was open-label, and the authors did not specify the total number of trigeminal neuralgia patients treated, making it difficult to assess their overall responder rate. 13 Limitations aside, these papers demonstrate ongoing efforts to expand the arsenal of treatments for this very painful disorder.…”
mentioning
confidence: 99%
“…Ambroxol is a very potent Nav blocker, approximately 40 times stronger than lidocaine [104], and probably preferentially blocks the subtype Nav1.8, which is responsible for repetitive firing and neuronal excitability [28,41]. Ambroxol has been studied in patients with different NP syndromes, including trigeminal neuralgia, and has shown relevant pain relief following topical administration of 20% ambroxol cream [42,105]. In a case series of CRPS patients, topical 20% ambroxol reduced spontaneous pain, edema, allodynia, hyperalgesia, and skin reddening and improved motor dysfunction and skin temperature [106].…”
Section: Ambroxolmentioning
confidence: 99%